Multilinear Calderón-Zygmund Operators and Their Commutators with BMO Functions in Herz-Morrey Spaces with Variable Smoothness and Integrability (Communications in Mathematical Research, 2019)
In this paper, we obtain that multilinear Calderón-Zygmund operatorsand their commutators with BMO functions are bounded on products of Herz-Morreyspaces with variable smoothness and integrability. The vector-valued setting of multilinear Calderón-Zygmund operators is also considered.
Keywords: multilinear Calderón-Zygmund operator; variable exponent; Herz-Morrey space; vector valued estimate